Keputusan Investasi di Era Digital melalui Peran Literasi Keuangan, Rasio Keuangan, Harga Wajar, dan Kemudahan Penggunaan Aplikasi Bibit - Novi Sentiya; Winda Winda; Lailatul Mukaromah; Munandar Munandar (Indonesian Accounting Literacy Journal, 2026)
This study examines how several key factors—financial literacy, financial ratios, fair price assessment, and the ease of using the Bibit—affect the investment decisions of users in stock investing. Bibit is the leading investment app in Indonesia, particularly popular among tech-savvy youth. Grounded in signal theory, this research employs a quantitative approach with a sample of 100 participants from various regions across Indonesia, selected through purposive sampling. In this context, the dependent variable (Y) represents investment decisions, while the independent variables comprise financial literacy (X1), financial ratios (X2), fair price valuation (X3), and user-friendliness of the Bibit app (X4). Data analysis was performed using multiple linear regression models with the assistance of the Jeffreys's Amazing Statistics Program (JASP). The results indicated that neither knowledge of fair price assessment nor ease of use significantly impacted investment decisions, with significance values of 0.267 and 0.445, respectively. In contrast, financial literacy and understanding of financial ratios emerged as significant influencers of investment choices, with significance values of 0.001 and 0.008, respectively, underscoring the critical importance of informed decision-making in today’s investment